Caribbean caught in the cross currents of globalization - Bernal, Richard L. (Institute of Social and Economic Research [Mona]JM, 1993)
Focuses on issues such as trends in the global economy, compatibility of regional trade blocs and multilateralism; the implications for the Caribbean; participation in multiple trade pacts; transition from preferential to reciprocal trade; and, strategic global repositioning.